Epigraphic Novelties from the South-East of the Iberian Peninsula III (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
This paper presents the epigraphic novelties from the peninsular southeast published between the years 2017 and 2020: a new reading of a coin legend from near Almodóvar del Río (Córdoba); seven short graffiti on pottery from Lezuza (Albacete); an inscription on a stone object from Puente Tablas (Jaén); an inscription on a fragment of lead, probably from La Mesa, Alcolea del Río (Sevilla); and an inscription on a bronze sheet of unknown provenance.
Keywords: epigraphic novelties; Southeastern Iberian; Turdetania; inscriptions on metal; inscriptions on stone and ceramic